Influence of pyrolytic seeds on ZnO nanorod growth onto rigid substrates for photocatalytic abatement of Escherichia coli in water - Sanchez, L (2014)
140-FINCYT-IB-2013/Concytec-403-2012/2011-02-CONCYTEC